Students’ perception on using teaching video in online learning during COVID-19 Pandemic / Ng Set Foong ...[et al.] - Ng, Set Foong; Ismail, Azianti; Tukiman, Norbaiti (Universiti Teknologi MARA, Kedah, 2021)
Since the outbreak of COVID-19, many higher educational institutions are shifting the conventional learning approach towards online learning to reduce the close contact in face-to-face classroom teaching. This paper examines student’s perception on using teaching video in online learning. Through this paper, twofold of objectives are carried out; (i) to investigate students’ experience in using teaching video in online learning and (ii) to investigate students’ preference on the characteristic of the teaching videos for their online learning. The online google form questionnaire was distributed through stratified random sampling to the groups of students who had practical experience in using teaching video in online learning. The data was analyzed using descriptive analysis by quantitative method. The findings show that majority of the students found that recorded teaching videos allow them to self-pace their learning. Most of the students prefer a short video that is less than 15 minutes, and they prefer their own lecturer voice rather than computer narration in the teaching videos. Overall, the students agreed that recorded teaching videos provided by their lecturers could assist them in their online learning.